Optimización de un proceso de inyección de agua en un campo del Magdalena Medio (2020)
Optimization of a water injection process in a field in Magdalena Medio, using the CMG simulator, varying injection rates, opening and closing of wells, conversion of wells, analysis of tracers, in order to generate an increase in the NPV and Recovery factor